Minimally invasive collection probe and methods for the use thereof - ZHANG JIALING; KATTA NITESH; GIESE NOAH; EBERLIN LIVIA; MILNER THOMAS (2020)
Method and devices are provided for assessing tissue samples from a plurality of tissue sites in a subject using molecular analysis. In certain aspects, devices of the embodiments allow for minimallyinvasive collection of liquid tissue samples and delivery of the samples for mass spectrometry analysis. 本发明提供了用于使用分子分析来评定来自受试者的多个组织部位的组织样本的方法和设备。在某些方面，各实施例的设备允许对液体组织样本进行微创收集并递送所述样本以进行质谱分析。